(untitled) (Italian Journal of Public Health, 2011)
Health insurance for poor people in the form of micro health insurance has emerged as a pathway to break the vicious circle of poverty in developing countries. Economists and policy analysts oppose micro health insurance on the grounds of the inherited feature of moral hazards in the insurance sector. In this paper we have tried to evaluate Rashtriya Swasthaya Bima Yojana (RSBY), an innovative mass level micro heath insurance initiative of the Indian Government that attempts to eradicate the healthcare problems of poor people. The results of the study shows that RSBY has helped to improve health outcomes of the poor population but, at the same time, the behavior of poor families towards the utilization of health care has also changed (a symptom caused by the presence of moral hazards). However, this changing behavior in the poor is morally and socially good and represents a step towards their attempt to improve their own living standard.